IMPLEMENTASI MODEL PROJECT BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA DI MIN 25 ACEH UTARA - Ilham fadillah Audeva (STKIP Subang, 2026)
This study aims to determine the implementation of the Project Based Learning (PjBL) model in improving the creative thinking skills of fourth-grade students at MIN 25 Aceh Utara in IPAS learning on energy transformation material. This research used a qualitative approach with the type of Classroom Action Research (CAR). The research was conducted in two cycles, and each cycle consisted of four stages, namely planning, action, observation, and reflection. The subjects of this study were 30 fourth-grade students at MIN 25 Aceh Utara. Data collection techniques used in this study were observation, tests, and documentation. Data analysis was conducted descriptively by calculating the percentage of student learning mastery. The results showed that the implementation of the Project Based Learning model could improve students' creative thinking skills. In the initial condition or pre-cycle, the number of students who achieved learning mastery was 8 students or 26.67%, with an average score of 50.00. In Cycle I, the number of students who achieved mastery increased to 13 students or 43.33%, with an average score of 67.67. In Cycle II, the number of students who achieved mastery increased significantly to 27 students or 90%, with an average score of 79.00. The implementation of Project Based Learning also increased student activity during the learning process. Students became more active in discussions, group work, expressing opinions, asking questions, presenting project results, and completing assignments. Students also demonstrated improvements in generating ideas, providing alternative solutions, presenting different ideas, and developing project results. Therefore, the implementation of the Project Based Learning model was effective in improving the creative thinking skills of fourth-grade students in IPAS learning on energy transformation material at MIN 25 Aceh Utara.